2010
DOI: 10.1002/path.2702
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aquaporin 5 increases proliferation and metastasis potential of lung cancer

Abstract: Water channel aquaporin 5 (AQP5) is highly expressed at the apical membrane of alveolar type I epithelial cells and confers high osmotic water permeability. AQP5 is also expressed in lung cancer tissue. Previous studies showed there was an up-regulation of AQP5 expression in cancer tissue compared to surrounding normal tissue. In addition, expression of AQP5 in lung cancer tissue was associated with poor prognosis. Herein, we tested the role of AQP5 in lung cancer oncogenesis and development. Lung cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
123
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 53 publications
11
123
0
Order By: Relevance
“…As possible mechanisms, the strength of the cytoskeleton or the membrane, or the expression of the Cl -channels may differ among these ESCC cell lines. Further, overexpression of several types of aquaporins (AQP), transmembrane water channel proteins which play an important role in transcellular water movement, has been reported in different types of human cancer (24)(25)(26)(27). cAMP has been reported to up-regulate AQP5 expression in lung epithelial cells, hence increasing water permeability (28).…”
Section: Discussionmentioning
confidence: 99%
“…As possible mechanisms, the strength of the cytoskeleton or the membrane, or the expression of the Cl -channels may differ among these ESCC cell lines. Further, overexpression of several types of aquaporins (AQP), transmembrane water channel proteins which play an important role in transcellular water movement, has been reported in different types of human cancer (24)(25)(26)(27). cAMP has been reported to up-regulate AQP5 expression in lung epithelial cells, hence increasing water permeability (28).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the present study suggested that AQPs, including AQP5, are involved in tumorigenesis. AQP5, a 21-24 kDa protein, was initially described as the main structural protein in caveolae and was believed to be a key molecule involved in oncogenic transformation and malignant progression (14,15). AQP5 plays an important regulatory role in several signaling pathways leading to cellular transformation, including those mediated by the Src family of tyrosine kinases, epidermal growth factor receptor, Wnt, and Erk1/2 (10,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that AQP-5 may be involved in differentiation of human gastric carcinoma cells, and overexpression of several aquaporins has been reported in different types of human carcinoma (8)(9)(10)(11)(12)(13)(14)(15)(16). However, the role of AQPs in biliary tract carcinogenesis has not yet been clearly defined.…”
Section: Introductionmentioning
confidence: 99%